Review for the management of vitamin B12 deficiency in diabetic patients on metformin - Sedeeq, Saad Thamer; Mohamed, Zohor Ahmed Kamaleldin; Al Fehaidi, Al Anoud Saleh; Al Tamimi, Mohammad Jamil Mohammad; Elhamid, Mohamed Abd; Muktar, Amina Ali Mohamed; Hamed, Ehab (International Journal of Research in Medical Sciences, 2020)
Long-term usage of Metformin is associated with lower serum vitamin B12 levels. The lower than normal levels could worsen neurological complications of diabetes, including diabetic neuropathy and poor cognition. Guidelines advise periodic monitoring of vitamin B12 but do not specify frequency, treatment targets or treatment modality. This commentary aims to review the prevalence and the severity of the presentation and to provide evidence-based answers to those clinical questions not answered by current guidelines.